Bundling up the Role of the Actin Cytoskeleton in Primary Root Growth - García-González, Judith; van Gelderen, Kasper (Frontiers in Plant Science, 2021)
Primary root growth is required by the plant to anchor in the soil and reach out for nutrients and water, while dealing with obstacles. Efficient root elongation and bending depends upon the coordinated action of environmental sensing, signal transduction and growth responses. The actin cytoskeleton is a highly plastic network that constitutes a point of integration for environmental stimuli and hormonal pathways. In this review we present a detailed compilation highlighting the importance of the actin cytoskeleton during primary root growth and we describe how actin binding proteins, plant hormones and actin disrupting drugs affect root growth and actin. We also discuss the feedback loop between actin and root responses to light and gravity. Actin affects cell division and elongation by controling of its own organization. We remark upon the importance of longitudinally-oriented actin bundles as a hallmark of cell elongation and the role of the actin cytoskeleton in protein trafficking and vacuolar reshaping during this process. The actin network is shaped by a plethora of actin binding proteins; however, there is still a large gap in connecting the molecular function of these proteins with their developmental effects. Here, we summarize their function and known effects on primary root growth with a focus on their high level of specialization. Light and gravity are key factors that help us understand root growth directionality. The response of the root to gravity relies on hormonal, particularly auxin, homeostasis and the actin cytoskeleton. Actin is necessary for gravity perception via the repositioning of sedimenting statoliths, but it is also involved in mediating the growth response via the trafficking of auxin transporters and cell elongation. Furthermore, auxin and auxin analogues can affect the composition of the actin network, indicating a potential feedback loop. Light affects actin organization and hence, root growth, although its precise role remains largely unknown. Recently, fundamental studies with the latest techniques have given us more in-depth knowledge of the role of and organization of actin in the coordination of root growth; however, there remains a lot to discover, especially in how actin organization helps cell shaping, and therefore root growth.